SEGS-1 a cassava genomic sequence increases the severity of African cassava mosaic virus infection in Arabidopsis thaliana - Rajabu, Cyprian A.; Dallas, Mary M.; Chiunga, Evangelista; De León, Leandro; Ateka, Elijah M.; Tairo, Fred; Ndunguru, Joseph; Ascencio-Ibanez, Jose T.; Hanley-Bowdoin, Linda (Frontiers in Plant Science, 2023)
Cassava is a major crop in Sub-Saharan Africa, where it is grown primarily by smallholder farmers. Cassava production is constrained by Cassava mosaic disease (CMD), which is caused by a complex of cassava mosaic begomoviruses (CMBs). A previous study showed that SEGS-1 (sequences enhancing geminivirus symptoms), which occurs in the cassava genome and as episomes during viral infection, enhances CMD symptoms and breaks resistance in cassava. We report here that SEGS-1 also increases viral disease severity in Arabidopsis thaliana plants that are co-inoculated with African cassava mosaic virus (ACMV) and SEGS-1 sequences. Viral disease was also enhanced in Arabidopsis plants carrying a SEGS-1 transgene when inoculated with ACMV alone. Unlike cassava, no SEGS-1 episomal DNA was detected in the transgenic Arabidopsis plants during ACMV infection. Studies using Nicotiana tabacum suspension cells showed that co-transfection of SEGS-1 sequences with an ACMV replicon increases viral DNA accumulation in the absence of viral movement. Together, these results demonstrated that SEGS-1 can function in a heterologous host to increase disease severity. Moreover, SEGS-1 is active in a host genomic context, indicating that SEGS-1 episomes are not required for disease enhancement.